Mercúrio, chumbo, arsênio e cádmio em camarões frescos e congelados coletados em três fazendas (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Trace metals are not obvious pollutants present in shrimp farm effluents. However, some trace metals are present as natural components in aquafeeds, as impurities in fertilizers or as active principles of pesticides, which can be accumulated in shrimp tissue. It were analyzed 90 muscle samples of fresh and frozen farmed shrimp and pond water collected in three farms in Brazil, between September 2008 and March 2011. It were determined total mercury concentrations by a flow injection mercury system and, lead, arsenic and cadmium concentrations by graphite furnace atomic absorption spectrophotometry. Mercury levels in the farmed shrimp ranged from 0.01 – 0.18 mg.kg-1 in fresh shrimp, and from 0.002 – 0.008 mg.kg-1 in frozen shrimp (wet weight). A similar behaviour was observed to lead concentrations, since frozen shrimp presented markedly lower lead concentrations (0.30 – 0.89 mg.kg-1) than fresh shrimp (0.92 – 2.89 mg.kg-1). In the case of arsenic, were observed concentrations of 0.01 – 0.77 mg.kg-1 in fresh shrimp muscle, and were no detected concentrations of this trace metal in muscle of frozen shrimp (Limit of detection of 0.002 mg.kg-1). The shrimp freezing process consists of a preliminary washing thoroughly in chlorinated water (5 ppm) to remove any remaining mud or sand, and to reduce bacterial contamination. The shrimp are drained as much as possible and are then ready for freezing through quick-freezing tunnel (individually quick frozen). There is no evidence indicating that this process contributed to the reduction of trace metals levels in frozen shrimp, but is clear that lead, arsenic and mercury levels are markedly lower in frozen than fresh shrimp. It was observed low concentrations of trace metals in pond water and also in shrimp muscle. In relation to the monitored years, in 2008 it was observed a slightly higher concentration of all trace metals in fresh shrimps compared to other years. Episodes of intensive precipitation caused recurrent devastating floods in the region in 2008, and caused harm to farms evaluated. Thus, increased concentrations of these trace metals in the rainy season may be related to resuspension of particles deposited in the sediment of the bottom in the ponds and therefore available for incorporation into these trace metals by aquatic biota. It can be concluded that farmed shrimp in Brazil is safe for human consumption. Thanks go to CNPq/ MAPA/SDA 577906/2008-9 for finantial support and scholarships conceded.